Factors Influencing Muslim Preference for Islamic Banking in Russia - Anita Priantina; Marina Tekueva; Aufa Aufa (Bank Indonesia, 2025)
This study analyzes factors influencing preference of Muslims in Russia to choose Islamic Banking. This is important as Russia has recently introduced Islamic banking into their national banking system. Modified Theory of Planned Behavior is used to structure the empirical model which is analyzed using SMART PLS4 with PLS-SEM method. Using data gathered from 476 respondents, the result shows that attitude, perceived behavioral control, and religiosity have significant influences on intention, and intention significantly influences the behavior of choosing Islamic Banking in Russia. However, subjective norms and trust are not significant. Educational campaigns incorporating norms and Islamic values, along with developing a special regulatory framework to ensure Sharia compliance, are recommended. Future studies may explore additional variables to enhance understanding of Islamic Banking practices in Russia.